THE RELEVANCE AND IMPORTANCE OF METHANE GAS ABSORBANTS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
In contemporary industrial, transportation, and energy systems, the utilization of high-pressure gases is expanding significantly. A critical challenge in these systems is the safe and efficient regulation of gas pressure.